Antennas for mobile and wireless communications and medical systems - Srifi, Mohamed Nabil (Université abdelmalek Essaadi, Faculté des sciences, Tétouan, 2009)
Mobile and wireless technologies have, as is also true with any other technology, some advanteges and benefits for their user but also some negative aspects and drawbacks. Radiofrequency energy may affect human health, either during wireless communications or in long term exposure to the radiation emitted from wireless, mobile or base stations. For instance, electromagnetic radiations from mobile phones may interfere with electronic equipement such as aeroplanes navigation systems and pacemakers.However, radiofrequency and microwaves may give promissing solutions for medical diagnosis and treatment of several diseases such as cancer.Therefire, wireless and mobile technologies can threaten human health as they can save lives. In the framework of this PhD Thesis, our research work focuses on two main research topics, namely, evaluation of RF/Microwaves effects on living tissues(e.g.human body), and antennas design for wireless and mibile communication and medical systems. Furthemore, a pedagogical approch was adopted, by giving all the underlying theoretical fundamentals(e.g.EM, antennas theory), by exposing basic concepts(e.g. simulations tools, wireless technologies) and reviewing the state of the art of all the technologies and issues investigated in this research work published in the speciallized literature. The interaction betwen RF/Microwaves radiations and human body was studied, based on a simple model composed by a dipole antenna and human head model.Several parameters affecting this interaction such as distance, frequency, water,eye, ear, etc are investigated.Our research interests focus on both RF/microwaves effects on human health and their medical applications where safety concerns regarding the biological effects of these radiations have been raised. Transmitting information with the highest data rates is the main challenge in current and future wirelmess and mobile technologies.Ultra wideband (UWB) tecchnology has been regarded as one of the most promising wireless technologies that would revolutionize wireless high data rate transmission with very high quality of services (QoS) to the end users. On the other hand, the miniaturization of mobile and wireless communication systems is one of the principal tendencies in this field .Ultra wideband antennas are essential for providing UWB wireless communications systems.In this research work, we have designed several planar UWB antennas for wireless and mobile communication and medical systems. Their design procedures have been discussed in detail. The prototypes of these antennas have been manufactured and their characteristics have been measured. Therefore , these antennas present very good candidates for those systems especially for their very attractive performances(i.e.low profile, low cost, nearly omni-directional radiation pattern,etc.).
Keywords: Electronic; Telecommunication; Wireless communication; Medical system; Radiofrequency radiation; Microwave on human health; Antenna; Ultra wideband